Literary and artistic process on the pages of "Alem-i Subyan" ("Children's World") - L.A. Memetova (Язык и текст, 2019)
In the recent decades, interest in the Crimean-Tatar periodicals of the late XIX and first half of the XX centuries has been intensified in the domestic scientific community, as to chronicles that have captured the literary background of the pre-war period. The modern researches in this area are the result of the consolidation of scientific forces to fill in the gaps in the historiography of Crimean Tatar philological thought. The purpose of the article is to review and analyze the literary and artistic process on the pages of the first specialized periodical for children in the Crimean Tatar language - the journal Alem-i Subyan ("Children's World"). The work analyzes original and translated creations published in various issues of the publication, assigns the individual works, defines the role of Alem-i Subyan ("Children's World"), which served as a platform for the presentation of the writers works' in the development of Crimean Tatar children's literature, and in general, in the evolution of the Crimean Tatar aesthetic thought early XX century. The implemented research contributes to the formation of the new knowledge in the history of the Crimean Tatar literature and in the development of the ethnic journalism.